Congenital anomalies of the kidney and urinary tract - Mahmoud, Anfal Hussain; Talaat, Iman M.; Tlili, Abdelaziz; Hamoudi, Rifat (Frontiers in Medicine, 2024)
Congenital Anomalies of the Kidney and Urinary Tract (CAKUT) refer to a range of conditions that affect the kidney and urinary tract. These anomalies can be severe, such as kidney agenesis, or milder, such as vesicoureteral reflux. CAKUT affects over 1% of live births and accounts for 40–50% of cases of chronic kidney failure in children. The pathogenesis of CAKUT is caused by various environmental, genetic, and epigenetic factors that disrupt normal nephrogenesis. Environmental factors that can lead to CAKUT include maternal diabetes, obesity, malnutrition, alcohol consumption, or medications affecting kidneys development. Genetic factors can cause an imbalance in the metanephros and the ureteric bud interaction. Defects in specific genes such as PAX2, TBX18, NRIP1, REX, SIX2, BMP4, and chromosome 17 cause CAKUT. Over 50 genes have been identified as the root cause of this condition, with monogenetic variants causing up to 20% of all cases. CAKUTs can be diagnosed through fetal ultrasonography, but some anomalies may remain undetected. GWASs, Next Generation Sequencing for targeted and whole exome DNA sequencing may provide additional diagnostic methods. This review article highlights some the leading factors that cause CAKUT, which adversely affects kidney development and urinary tract function.